Environmental consciousness, health consciousness and ethical identity to achieve sustainable rehabilitation after disaster - Setiawan Margareth; Sadeli Dian; Hajar Mohamad Siti (E3S Web of Conferences)
This study examines the influence of environmental consciousness, health consciousness, and ethical identity on fostering sustainable restoration following disasters. As global environmental and health challenges escalate, the incorporation of sustainable practices is imperative not just in daily consumption but also in post-disaster recovery initiatives. This study investigates the impact of individual and community awareness in these three domains on the sustainable rehabilitation of impacted areas. This study utilizes a dataset of 200 respondents from Indonesia and implements Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the influence of consciousness elements on sustainability consciousness, essential for long-term rehabilitation. Research indicates that health and environmental consciousness significantly influence sustainability consciousness, while ethical identity does not demonstrate a considerable effect. The study emphasizes the necessity of incorporating environmental and health consciousness into disaster recovery efforts, offering pragmatic insights for politicians and humanitarian organizations to promote sustainable rehabilitation practices.